EFFECT OF PROFIT MANAGEMENT, FINANCIAL RATIO AND CORPORATE GOVERNANCE MECHANISM ON BOND RATING - Rizka Dewi Oktaviyani (Jurnal Ekonomi, 2021)
Bond ratings issued by rating agencies assist investors in selecting bonds. Bond ratings are very useful for investors and issuers, namely providing information about the company's ability to pay off the bonds issued. The rating issued gives a signal to investors on the quality and risk of a bond. The rating process is carried out by the rating agency by taking into account various factors, such as financial factors through financial ratios, earnings management measures and corporate governance mechanisms. This study aims to provide empirical evidence that earnings management, financial ratios and corporate governance mechanisms affect bond ratings. The subjects of this research are companies listed on the Indonesia Stock Exchange and listed on PT. PEFINDO 2008-2011. The sample selection was done by purposive sampling method, in order to obtain 11 companies that meet the criteria with 4 years of observation. The data used in the form of secondary data derived from the financial statements and bond rating database of PT. PEFINDO, while the data analysis used logistic regression analysis. The results show that earnings management, liquidity ratios, managerial ownership and audit quality have an effect on bond ratings. Meanwhile, the activity ratio, market value ratio, institutional ownership and independent commissioners have no effect on bond ratings. The conclusion of this study is that of the 8 variables used in this study only earnings management variables, liquidity ratios, managerial ownership and audit quality can be used to predict a company's bond rating. Suggestions that can be given are that the next researcher can replace the research sample using financial companies, add a complete corporate governance variable and be careful in interpreting a company's financial ratios.